THE EFFECT OF MARKETING MIX ON TOURIST DECISION IN MANDEH ISLAND WEST SUMATRA, INDONESIA - Antoni, Antoni; Yuliviona, Reni; Kamela, Ice; Muslim, Irwan (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract: The study aims to find out the influence of the marketing mix consisting of promotion, product, price, place, people, process and physical evidence against the decision of the tourists visiting the attractions located at Painan Mandeh island, West Sumatra. The sample in this study are tourists visiting sights Mandeh with total sample as many as 90 people. Sampling technique was purposive sampling. The type of data in this study is the primary data of the dissemination of the questionnaire. The results of this study found that physical evidence of significant and influential promotion, product, price, place, person while the process is not significant effect against the decision of tourists visit. Keywords : Promotion; produkct; price; place; proces; person tangible;, tourist; Smart PLS JEL Classification Code : M31; F10; J01; Z30;Z32